Magnetic Resonance Imaging Detection of Intraplaque Hemorrhage. (3rd March 2017) - McNally, J Scott; Kim, Seong-Eun; Mendes, Jason; Hadley, J Rock; Sakata, Akihiko; De Havenon, Adam H; Treiman, Gerald S; Parker, Dennis L
Carotid artery atherosclerosis is a major cause of ischemic stroke. For more than 30 years, future stroke risk and carotid stroke etiology have been determined using percent diameter stenosis based on clinical trials in the 1990s. In the past 10 years, magnetic resonance imaging (MRI) sequences have been developed to detect carotid intraplaque hemorrhage. By detecting carotid intraplaque hemorrhage, MRI identifies potential stroke sources that are often overlooked by lumen imaging. In addition, MRI can dramatically improve assessment of future stroke risk beyond lumen stenosis alone. In this review, we discuss the use of heavily T1-weighted MRI sequences used to detect carotid intraplaque hemorrhage. In addition, advances in ciné imaging, motion robust techniques, and specialized neck coils will be reviewed. Finally, the clinical use and future impact of MRI plaque hemorrhage imaging will be discussed.